2011
DOI: 10.1007/s11224-011-9755-6
|View full text |Cite
|
Sign up to set email alerts
|

Computational studies on tetrazole derivatives as potential high energy materials

Abstract: The tetrazole is an important functionality of the most of energetic materials due to 80% nitrogen content, stability, and high enthalpy of formation. The present structure-property relationship study focuses on the optimized geometries of tetrazole derivatives obtained from density functional theory (DFT) calculations at B3LYP/6-31G* levels. The heat of formation (HOF) of tetrazole derivatives have been calculated by designing the appropriate isodesmic reactions. The increase in nitro groups on azole rings sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 61 publications
1
11
1
Order By: Relevance
“…Densities predicted using the cvff force field (Table 3) were used to calculate detonation characteristics, as they lead to marginally better results for nitro compounds [40,41]. The predicted density of the MTNI molecule (1.82 g/cm 3 ) using the cvff force field was to be found close to the experimental value (1.79 g/cm 3 ) [42].…”
Section: Densitymentioning
confidence: 88%
See 1 more Smart Citation
“…Densities predicted using the cvff force field (Table 3) were used to calculate detonation characteristics, as they lead to marginally better results for nitro compounds [40,41]. The predicted density of the MTNI molecule (1.82 g/cm 3 ) using the cvff force field was to be found close to the experimental value (1.79 g/cm 3 ) [42].…”
Section: Densitymentioning
confidence: 88%
“…Hence, the basis set 6-31 G* was chosen for further studies. Previous studies have shown that B3LYP/6-31 G* methods produce more reliable enthalpies of formation [38][39][40][41].…”
Section: Heat Of Formationmentioning
confidence: 99%
“…show that the increase in nitro groups in a molecule improves the density and it also increases the chances of inter-and intramolecular hydrogen bonding between acidic hydrogen and oxygen present in molecule [34][35][36][37]. This clearly indicates that the -NO 2 group is an effective substituent for improving densities of the energetic materials.…”
Section: Oxygen Balance and Densitymentioning
confidence: 88%
“…The heat of formation for 49 tetrazole derivatives was computed using density functional theory [11]. Since tetrazole derivatives have broad applications in medicine, biology, agriculture and in ammunitions [12][13][14][15] therefore there is a continuous surge for newer application of tetrazole and its derivatives [16][17][18][19][20]. In the present work, an interesting compound of the tetrazole family, 7a-Aza-B-homostigmast-5-eno [7a, 7-d],…”
Section: Introductionmentioning
confidence: 99%